2022
DOI: 10.4103/jfmpc.jfmpc_1139_21
|View full text |Cite
|
Sign up to set email alerts
|

COVID 19 Pandemic and biomedical waste management practices in healthcare system

Abstract: The whole world was shaken with the pandemic of Coronavirus Disease (COVID-19) in end of the year 2019. Due to its novel origin, it was required to follow all precautions possible. Dealing with the massive amount of infectious healthcare waste became an enormous challenge. This review identifies the impacts of the pandemic on biomedical waste management. This systematic review was made by using keywords “biomedical waste” and “COVID 19” in open access databases like PubMed, Science Direct, Scopus, Google Schol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 67 publications
(133 reference statements)
0
6
0
Order By: Relevance
“…Monthly data for monitoring segregation at the point of generation that was, at all the 115 bins of different areas were collected. The average daily BMW segregation deficiency (BMWSD) index was calculated and all areas were arranged in descending order for the month zero (0), three (3) and six (6) for top deficiency areas (Table 1). 1,2 Based on number of areas, it was found that on zeroth month there were 16 areas where some deficiency was detected during daily round.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Monthly data for monitoring segregation at the point of generation that was, at all the 115 bins of different areas were collected. The average daily BMW segregation deficiency (BMWSD) index was calculated and all areas were arranged in descending order for the month zero (0), three (3) and six (6) for top deficiency areas (Table 1). 1,2 Based on number of areas, it was found that on zeroth month there were 16 areas where some deficiency was detected during daily round.…”
Section: Resultsmentioning
confidence: 99%
“…2 As hospitals were mostly service oriented industry and attrition rate was quite high comparing to other industry specially for nursing, housekeeping and doctor, the main pillars of the hospital. [5][6][7] Continuous monitoring and training will be the main focus for any hospital for providing better and better patient care even in some difficult times also. 8,9 The limitation of this study were not all the patient care areas were included and only working days data could be captured due to lack of manpower.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that before the pandemic hit, the average quantity of biomedical waste produced was 0.5 kg/bed/day, which increased to 3.4 kg/bed/day during the pandemic (Mondal et al 2022 ). Improper handling and disposal of contaminated waste could cause the unintentional spread of the infectious virus.…”
Section: Socio-economic Environmental and Health Implications Of The ...mentioning
confidence: 99%
“…The COVID-19 pandemic has now transformed healthy societies worldwide into diseased ones, resulting in a very high number of 1 2 deaths. It also created one significant problem: improper handling of the medical waste produced in the testing and treatment of the disease [6]. In India, BMW generated due to COVID-19 contributed to about 126 tonnes per day out of the 710 tonnes of waste produced daily [7].…”
Section: Introductionmentioning
confidence: 99%